DETERMINASI PROFITABILITAS PERUSAHAAN ASURANSI KONVENSIONAL YANG TERDAFTAR DI BEI - Nurhayati Nurhayati; Poltak Parulian Sitompul (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2021)
The insurance mechanism is basically a risk transfer from the insured (policy holder community) to the insurer (insurance company), and for their willingness to ensure the risk, the company benefits from the premium offered. Insurance companies are also non-bank financial institutions that have an intermediary function to channel funds from surplus spending units to deficit spending units. The concept that is run by insurance companies in seeking profit or profit is to sell services. Basically, the company does not receive a service fee because the risk of the insured is the original risk insurer and is transferred to the insurance company as the insurer. Profitability is measured through several financial ratios, one of which is Return on Assets (ROA). Using 10 companies with the model chosen is the Fixed Effect Mode. Some research results, the researcher wants to do research on the factors that affect the profitability of conventional insurance companies listed on the IDX. Based on the test results using 10 companies with the model chosen is the Fixed Effect Model with the results of all variables having a significant effect on ROA, where DER and RT have a negative effect and CT has a positive effect.